Design and Analysis of a Pitch Fatigue Detection System for Adaptive Baseball Learning - Ma, Yi-Wei; Chen, Jiann-Liang; Hsu, Chia-Chi; Lai, Ying-Hsun (Frontiers in Psychology, 2021)
Owing to the rapid development of information and communication technologies, such as the Internet of Things, artificial intelligence, and computer vision, in recent years, the concept of smart sports has been proposed. A pitch fatigue detection method that includes acquisition, analysis, quantification, aggregation, learning, and public layers for adaptive baseball learning is proposed herein. The learning determines the fatigue index of the pitcher based on the angle of the pitcher’s elbow and back as the number of pitches increases. The coach uses this auxiliary information to avoid baseball injuries during baseball learning. Results show a test accuracy rate of 89.1%, indicating that the proposed method effectively provides reference information for adaptive baseball learning.